Experience in the Use of Social Media in Medical and Health Education - Paton, C.; Bamidis, P. D.; Eysenbach, G.; Hansen, M.; Cabrer, M. (Yearbook of Medical Informatics, 2011)
Social media are online tools that allow collaboration and community building. Succinctly, they can be described as applications where “users add value”. This paper aims to show how five educators have used social media tools in medical and health education to attempt to add value to the education they provide.We conducted a review of the literature about the use of social media tools in medical and health education. Each of the authors reported on their use of social media in their educational projects and collaborated on a discussion of the advantages and disadvantages of this approach to delivering educational projects.We found little empirical evidence to support the use of social media tools in medical and health education. Social media are, however, a rapidly evolving range of tools, websites and online experiences and it is likely that the topic is too broad to draw definitive conclusions from any particular study. As practitioners in the use of social media, we have recognised how difficult it is to create evidence of effectiveness and have therefore presented only our anecdotal opinions based on our personal experiences of using social media in our educational projects.The authors feel confident in recommending that other educators use social media in their educational projects. Social media appear to have unique advantages over non-social educational tools. The learning experience appears to be enhanced by the ability of students to virtually build connections, make friends and find mentors. Creating a scientific analysis of why these connections enhance learning is difficult, but anecdotal and preliminary survey evidence appears to be positive and our experience reflects the hypothesis that learning is, at heart, a social activity.
Keywords: Social media; web 2.0; medical education; conferences 2.0; mhealth